Do Neuroscience Journals Accept Replications? A Survey of Literature - Yeung, Andy W. K. (Frontiers in Human Neuroscience, 2017)
Background: Recent reports in neuroscience, especially those concerning brain-injury and neuroimaging, have revealed low reproducibility of results within the field and urged for more replication studies. However, it is unclear if the neuroscience journals welcome or discourage the submission of reports on replication studies. Therefore, the current study assessed the explicit position of neuroscience journals on replications. Methods: A list of active neuroscience journals publishing in English was compiled from Scopus database. These journal websites were accessed to read their aims and scope and instructions to authors, and to assess if they (1) explicitly stated that they accept replications; (2) did not state their position on replications; (3) implicitly discouraged replications by emphasizing on the novelty of the manuscripts; or (4) explicitly stated that they reject replications. For journals that explicitly stated they accept or reject replications, their subcategory within neuroscience and their 5-year impact factor were recorded. The distribution of neuroscience replication studies published was also recorded by searching and extracting data from Scopus. Results: Of the 465 journals reviewed, 28 (6.0%) explicitly stated that they accept replications, 394 (84.7%) did not state their position on replications, 40 (8.6%) implicitly discouraged replications by emphasizing on the novelty of the manuscripts, and 3 (0.6%) explicitly stated that they reject replications. For the 28 journals that explicitly welcomed replications, three (10.7%) stated their position in the aims and scope, whereas 25 (89.3%) stated in within the detailed instructions to authors. The five-year impact factor (2015) of these journals ranged from 1.655 to 10.799, and nine of them (32.1%) did not receive a 5-year or annual impact factor in 2015. There was no significant difference in the proportions of journals explicitly welcomed replications (journals with versus without impact factors, or high versus low impact factors). All sub-categories of neuroscience had at least a journal that welcomed replications. Discussion: The neuroscience journals that welcomed replications and published replications were reported. These pieces of information may provide descriptive information on the current journal practices regarding replication so the evidence-based recommendations to journal publishers can be made.